Inovasi Administrasi Kehadiran Santri di TPA: Solusi Cerdas dengan Teknologi Sidik Jari dan Firebase - Tiara Muqasonah; Hendra Hendra; Ocsirendi Ocsirendi; Novitasari Novitasari (Jurnal Inovasi Teknologi Terapan, 2026)
Student attendance administration is a crucial process at Al-Quran Education Parks (TPA). In reality, many TPAs ​​still conduct manual administration, as in the three TPAs ​​surveyed in Bangka, making them vulnerable to data loss, inaccurate recording, and slow processing. The solution is to design an intelligent, integrated website attendance system using fingerprint sensors, ESP 8266, and Firebase. The collaboration between biometric technology and Firebase is expected to replace manual administration, improve discipline and accuracy of student attendance data, and increase efficiency. The results demonstrate the system's effectiveness in supporting the attendance process.